Model Implementasi Sistem Informasi Pemerintah Daerah di Provinsi Gorontalo Berdasarkan Pemodelan Persamaan Struktural: Peran Komitmen dan Dukungan Organisasi, Kapasitas Sumber Daya Manusia, dan Kesiapan Teknologi - Firmansyah Yusuf; Dedi Budiman Hakim; A. Faroby Falatehan (Research and Development Agency Ministry of Home Affairs, 2026)
Since the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 70 of 2019 required all regional governments to adopt the Regional Government Information System (SIPD), the system has been expected to be fully integrated into planning, budgeting, and reporting at every regional agency. In practice, an obligation on paper has not automatically been matched by readiness in the field. In Gorontalo province, SIPD administrators across various regional agencies still contend with a range of problems, from uneven technical understanding to institutional support that varies markedly across agencies. This study analyzes three factors thought to affect the effectiveness of SIPD implementation: organizational commitment and support, human resource capacity, and technology readiness. Data were collected from 125 SIPD administrators across regional agencies throughout Gorontalo province through a questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM). Human resource capacity emerged as the most decisive factor. Organizational commitment and support ranked second, because even the best system requires consistent institutional backing rather than the competence of individual users alone. Technology readiness showed a positive but statistically non-significant association, most likely because technological infrastructure in Gorontalo is already relatively adequate. In other words, the current barriers to SIPD implementation are no longer about devices or networks but about people and organizational governance.